Effect of Supplementation of Exogenous Fibrolytic Enzymes in Total Mixed Ration on Rumen Fermentation Pattern in Dairy Cows - Lunagariya, P.M.; Shah, S.V.; Gupta, R.S.; Parnerkar, Subhash; Pansuriya, Hiren; Khaire, Kashmira; Patel , G.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The study was planned to evaluate the effect of exogenous fibrolytic enzymes (EFE) supplementation for 56 days @ 240 mg/kg total mixed ration (TMR) on rumen fermentation in dairy cows. For this six dry non-pregnant cows were assigned in each treatment with and without EFE. The rumen metabolites were evaluated on last day of experiment. About 250 ml rumen liquor was collected from each cow at pre-feeding and at 2, 4 and 6 h post-feeding. Strained Rumen Liquor (SRL) pH of cows was 6.78 and 6.70; and total volatile fatty acids (TVFAs) concentration was 8.85 and 11.22 mM/dl, respectively for cows fed TMR without enzymes (control T1) and TMR with fibrolytic enzymes (T2) with significant difference (P
Keywords: Cows; Exogenous fibrolytic enzymes; Total mixed ration; Rumen fermentation